DOMESTIKSASI PEREMPUAN DALAM CERAMAH USTAZ FIRANDA ANDIRJA: KAJIAN WACANA FAIRCLOUGH - Made Made (sarasvati, 2020)
This study aims to describe the domestication of women in Ustaz Firnanda Andirja's lecture. This study uses Norman Fairclough's discourse theory to analyze text descriptively, interpretatively, and explain. This research focuses on lectures on the topic as bad as your wives, women in heaven like to stay at home, and use what your husband likes, even if you don't like it yourself. The results of this study found that Ustaz Firnanda Andrija's lecture had an influence that could change the viewpoint of life of the audience and worshipers who attended the lecture. Women should stay at home and not go against their husbands orders as absolute power holders. Ustaz Firnanda also helped strengthen the dominance of men over women (especially in the family).